From design to the clinic: practical guidelines for translating cardiovascular nanomedicine. Issue 13 (27th August 2018) - Cicha, Iwona; Chauvierre, Cédric; Texier, Isabelle; Cabella, Claudia; Metselaar, Josbert M; Szebeni, János; Dézsi, László; Alexiou, Christoph; Rouzet, François; Storm, Gert; Stroes, Erik; Bruce, Donald; et al.
Abstract: Cardiovascular diseases (CVD) account for nearly half of all deaths in Europe and almost 30% of global deaths. Despite the improved clinical management, cardiovascular mortality is predicted to rise in the next decades due to the increasing impact of aging, obesity, and diabetes. The goal of emerging cardiovascular nanomedicine is to reduce the burden of CVD using nanoscale medical products and devices. However, the development of novel multicomponent nano-sized products poses multiple technical, ethical, and regulatory challenges, which often obstruct their road to successful approval and use in clinical practice. This review discusses the rational design of nanoparticles, including safety considerations and regulatory issues, and highlights the steps needed to achieve efficient clinical translation of promising nanomedicinal products for cardiovascular applications.